2018
DOI: 10.1093/aje/kwy112
|View full text |Cite
|
Sign up to set email alerts
|

New-Onset Asthma and Combat Deployment: Findings From the Millennium Cohort Study

Abstract: Recent reports suggest US military service members who deployed in support of the recent conflicts in Iraq and Afghanistan have higher rates of new-onset asthma than those who did not deploy. However, it is unknown whether combat experiences, in addition to deployment, contribute to new-onset asthma risk. This study aimed to longitudinally determine the risk factors for developing asthma, including combat deployment (categorized as deployed with combat experience, deployed without combat experience, or nondepl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 38 publications
(22 reference statements)
2
13
0
1
Order By: Relevance
“…Case series describing the evaluation of symptomatic military personnel do not note any single etiology, emphasizing the importance of a comprehensive clinical assessment, but asthma has been a common finding (References 8 and 75 and S. D. Krefft, workshop presentation of unpublished data). This is consistent with epidemiologic findings from the Millennium Cohort Study that demonstrate an increased risk of new-onset asthma (by self-report) related to combat exposure during deployment ( 9 ) and the observational findings in which approximately half of the deployed persons discharged with asthma after deployment did not have a previous known diagnosis ( 10 ). Nonetheless, a number of questions remain regarding the drivers of increased healthcare use for respiratory conditions and potential under- and overdiagnosis of specific conditions.…”
Section: Summary and Key Questionssupporting
confidence: 89%
See 1 more Smart Citation
“…Case series describing the evaluation of symptomatic military personnel do not note any single etiology, emphasizing the importance of a comprehensive clinical assessment, but asthma has been a common finding (References 8 and 75 and S. D. Krefft, workshop presentation of unpublished data). This is consistent with epidemiologic findings from the Millennium Cohort Study that demonstrate an increased risk of new-onset asthma (by self-report) related to combat exposure during deployment ( 9 ) and the observational findings in which approximately half of the deployed persons discharged with asthma after deployment did not have a previous known diagnosis ( 10 ). Nonetheless, a number of questions remain regarding the drivers of increased healthcare use for respiratory conditions and potential under- and overdiagnosis of specific conditions.…”
Section: Summary and Key Questionssupporting
confidence: 89%
“…There was also no statistical association in this analysis with self-reported incident asthma, chronic bronchitis, or emphysema. Subsequent and longer follow-up of a larger number of Millennium Cohort Study participants followed through 2013 ( n = 77,770) revealed an increased risk of respondent-reported new onset of health professional–diagnosed asthma for those with deployment-related combat experience compared with those who did not deploy ( 9 ). The RR of new-onset asthma was similar for men (RR, 1.30; 95% CI, 1.14–1.47) and women (RR, 1.24; 95% CI, 1.05–1.46) after adjustment for multiple covariates that included smoking, body mass index (BMI), rank, branch, and post-traumatic stress disorder status.…”
Section: Epidemiologic and Observational Studies In Previously Deploymentioning
confidence: 99%
“…Case series describing the evaluation of symptomatic military personnel do not note any single etiology, emphasizing the importance of a comprehensive clinical assessment, but asthma has been a common finding (References 8 and 75 and S. D. Krefft, workshop presentation of unpublished data). This is consistent with epidemiologic findings from the Millennium Cohort Study that demonstrate an increased risk of newonset asthma (by self-report) related to combat exposure during deployment (9) and the observational findings in which approximately half of the deployed persons discharged with asthma after deployment did not have a previous known diagnosis (10). Nonetheless, a number of questions remain regarding the drivers of increased healthcare use for respiratory conditions and potential under-and overdiagnosis of specific conditions.…”
Section: Adverse Respiratory Health Effectssupporting
confidence: 86%
“…There was also no statistical association in this analysis with selfreported incident asthma, chronic bronchitis, or emphysema. Subsequent and longer follow-up of a larger number of Millennium Cohort Study participants followed through 2013 (n = 77,770) revealed an increased risk of respondent-reported new onset of health professional-diagnosed asthma for those with deployment-related combat experience compared with those who did not deploy (9). The RR of newonset asthma was similar for men (RR, 1.30; 95% CI, 1.14-1.47) and women (RR, 1.24; 95% CI, 1.05-1.46) after adjustment for multiple covariates that included smoking, body mass index (BMI), rank, branch, and post-traumatic stress disorder status.…”
Section: Prospective Cohort Studiesmentioning
confidence: 99%
See 1 more Smart Citation